STRATEGI GURU DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV DI MADRASAH IBTIDAIYAH - Wulan Fitriana; Rahmiaty (STKIP Subang, 2026)
The importance of teachers’ strategies in developing critical thinking skills at the elementary school level is a fundamental necessity for addressing the educational challenges of the 21st century. This study aims to analyze teachers’ strategies in developing critical thinking skills among fourth-grade students and to identify indicators of critical thinking skills that emerge in students as a result of the application of these strategies. The study was conducted at MIN 3 in Lhokseumawe using a qualitative approach with a descriptive research design. Data collection techniques included in-depth interviews with fourth-grade homeroom teachers, passive participant observation during four class sessions, and documentation. The results of the study indicate that the strategies used by teachers to develop students’ critical thinking skills include: (1) Adaptive Expository and Contextual Learning Strategies, (2) Strategies for Creating a Comfortable and Conducive Classroom Atmosphere, and (3) Scaffolding Strategies for Passive Students. According to Facione, the indicators of critical thinking that are already well-developed are interpretation; those that are beginning to develop are inference, explanation, and analysis; and those not yet evident are evaluation and self-regulation.